Winner or loser - what makes the difference? Analysis of the European Championships 2000 to 2006 in men`s handball - Wiemeyer, J.; Heinz, M. (World Congress of Performance Analysis of Sport VIII, 2008)
The results show that there are selected invariant factors of a match determining win or loss. These factors are saves in position attacks and goals from 9m shots. In general, one can conclude that being successful both in avoiding goals of the opponent in the standard defensive situation and scoring goals from the back are variables that may be considered the `basic invariant features` of the antagonistic structure of the handball game. On the other hand there are variables that are specific to one or two championships. These variables may be considered as `short-term fashion` in the development of handball tactics. Accepting this view one can conclude that in the EURO2000 variables of defensive tactics dominated the game, whereas offensive tactics were more important in the EURO2002 and 2004. Due to the development of the game, in the EURO2006 steals became more important. This indicates that the fast switch from defence to offense played a decisive role in EURO2006. Finally, some limits of the proposed approach should be considered. Analyzing the `surface` variables of the match without taking into account the `deep` structures and the specific situational context yields only a very crude picture of the handball game. Furthermore, there are no tests of reliability of the scoring system.